Democratic approaches to environmental education: Dream or possibility? - Jo-Anne Ferreira (Environmental Association of Southern Africa, 1997)
Research indicates that few teachers are currently using a democratic approach to teaching in environmental education even though much of the environmental education literature supports and encourages such an approach. Various explanations are offered for this situation although all agree that the principles, goals and processes of democratic pedagogy are often antithetical to the processes of contemporary schooling. Based on a case study of an attempt at democratic pedagogy in an Australian primary school, this paper explores some of the factors that may influence, assist or constrain teachers in their efforts to implement democratic approaches and strategies in the teaching of environmental education.